Will changes in sorghum processing improve broiler chick performance - Seitz, Daniel (Kansas State University, 2019)
Grain sorghum is an ingredient that may be included in broiler chicken diets. However, when compared to corn, the utilization of energy in sorghum is inadequate. Sorghum contains kafirin, phenolic compounds, and phytate. These factors are considered part of the reason why sorghum has decreased energy utilization. Another factor effecting sorghum energy utilization is its vulnerability to “moist heat.” Two experiments were conducted to test the effects of particle size, conditioning temperature, and the inclusion on sodium metabisulfite in sorghum-based diets for broiler chickens. In the first experiment it was found that a finely ground sorghum had increased gain:feed ratio (G:F) and body weight gain compared to other particle sizes independent of conditioning temperature. Gain:feed ratio was significantly improved when conditioning temperature was 65.5°C compared to 93°C. In the second experiment sodium metabisulfite was added to diets pelleted at 2 conditioning temperatures. The inclusion of sodium metabisulfite at 1.75 g/kg of the finished diet lead to a significantly lower feed efficiency. Sodium metabisulfite may be beneficial but it may also require a higher inclusion level. The results of these studies indicate that sorghum may be added to broiler rations but processing at higher temperatures can negatively impact nutrient utilization.
Keywords: Sorghum; Broiler; Sodium metabisulfite